Spark plasma sintering of polycrystalline La0.6Ce0.3Pr0.1B6–ZrB2 composites. Issue 3 (28th November 2022) - Wang, Yan; Bao, Yan; Luo, Shifeng; Han, Cuiliu; Yang, Xinyu; Zhang, Jiuxing
Abstract: This paper has studied the densification, microstructure, and properties of polycrystalline La0.6 Ce0.3 Pr0.1 B6 –ZrB2 composites prepared by spark plasma sintering (SPS). The highest relative density of 98.7% is obtained at the SPS condition of axial mechanical pressure 50 MPa, sintering temperature 1900°C and holding time 5 min. The Vickers hardness decreases linearly from the maximum value of 21.49 GPa to the value of 8.24 GPa with the tested temperature increased from room temperature to 1000°C. The effects of crack deflection and bridging have resulted in the fracture toughness of 4.56 MPa m 1/2 of dense polycrystalline La0.6 Ce0.3 Pr0.1 B6 –ZrB2 composite. The J 1kV of 7.02 A/cm 2 obtained at 1600°C, the work function of 2.743 eV determined by ultraviolet photoelectron spectroscopy, and the good oxidation resistance below 1100°C in air have revealed that the dense polycrystalline La0.6 Ce0.3 Pr0.1 B6 –ZrB2 composite has a good potential to be a promising hot cathode material.